Optimizing After-Sales Services in the Automotive Maintenance Sector: A Lean Manufacturing and MRP Case Study in Peru - Harboe-Chaman, Pablo (2025)
This research aims to improve productivity and customer satisfaction in the automotive maintenance sector in Peru, which faces problems such as inefficiency in after-sales services and poor inventory management. The methodology involves the integration of lean manufacturing tools—including 5S, material requirements planning (MRP), standardized work, among others. The implementation of these tools seeks to optimize workspace organization, improve inventory management, and streamline service operations. The main results revealed a 20,37 % reduction in downtime, a decrease in stockouts from 11,81 % to 3,58 %, and a reduction in cycle time from 3 hours and 15 minutes to 1 hour and 36 minutes. These advancements contributed to a significant increase in customer satisfaction, as evidenced in the rise of NPS from 46 % to 79 %. Exploring the use of digital technologies such as IoT and AI is suggested to achieve further improvements.